Botulinum toxin A injection for the treatment of neurogenic detrusor overactivity secondary to spinal cord injury: Multi‐institutional experience in Japan. (18th November 2014) - Sengoku, Atsushi; Okamura, Kikuo; Kimoto, Yasusuke; Ogawa, Takatoshi; Namima, Takashige; Yamanishi, Tomonori; Yokoyama, Teruhiko; Akino, Hironobu; Maeda, Yoshiko
<x xml:space="preserve">Abstract</x> Objectives To examine the efficacy and safety of onabotulinumtoxinA (Botox) injection into the bladder wall for the treatment of neurogenic detrusor overactivity secondary to spinal cord injury in Japanese patients. Methods We enrolled Japanese spinal cord injury patients with cystometrically confirmed neurogenic detrusor overactivity who experienced urinary incontinence at least once a week either because they were refractory to anticholinergics or had to discontinue treatment because of adverse events. Patients received 200 units of onabotulinumtoxinA injected into the bladder wall after a 2‐week washout of anticholinergics, and urodynamic variables were assessed before and 1 month after injection. Catheterization and urinary incontinence data, as well as International Consultation on Incontinence Questionnaire – Short Form scores, were assessed before injection and every month thereafter until the cessation of treatment effects. Results The study enrolled 19 patients (13 men, six women, age range 22–67 years). One month after injection, the mean number of urinary incontinence episodes decreased from 4.3 to 1.5 times/day (P = 0.004), and the maximum cystometric capacity increased from 100 mL to 296 mL (P = 0.0004). The rate of effective cases whose daily urinary incontinence frequency was decreased to less than 50% was 74%. The duration of efficacy without anticholinergic medication ranged from 3 to 12 months (median 8.5 months). Clinically significant adverse events were not observed. Conclusions The present findings show the efficacy and tolerability of onabotulinumtoxinA injection for the treatment of neurogenic detrusor overactivity in Japanese spinal cord injury patients.